Tathbiq Namadzij Ta’allum “al-Fushul al-Maqlubah” li Ta’lim Maharah al-Kalam fi al-Lughah al-Arabiyyah - Maesaroh, Miftakhul (UIN Syekh Wasil Kediri, Indonesia, 2020)
Speaking skills which are productive language skills become one of the objectives of Arabic learning. Various models of approaches and methods are used to improve this skill. Flipped classroom is a learning model that turns away from the traditional model. With this learning model it is hoped that learning is more effective so that it helps stude nts to master speaking skills more easily and pleasantly. The purpose of writing this article is to describe the learning model of Flipped classroom in speaking skills learning. The research method used is field-qualitative research methods. With the results of the study that the Flipped classroom learning model can be applied in speaking skills learning by following three main stages, namely preparation, implementation, and evaluation.